2013
DOI: 10.1647/2012-010
|View full text |Cite
|
Sign up to set email alerts
|

Osteoma in a Blue-Fronted Amazon Parrot (Amazona aestiva)

Abstract: Osteoma is an uncommon bone formation documented in avian species and other animals. A blue-fronted Amazon parrot (Amazona aestiva) with clinical respiratory symptoms was examined because of a hard mass present on the left nostril. Radiographs suggested a bone tumor, and the mass was surgically excised. Histopathologic examination revealed features of an osteoma. To our knowledge, this is the first description of an osteoma in a blue-fronted Amazon parrot. Osteoma should be considered as a differential diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…The overall avian neoplasm rate in the literature analysis was 2.3% (3298/144,277 birds; Supplementary Table S1) indicating that neoplasms are rare among birds, as also suggested by others [65][66][67] . Although neoplastic diseases are not well studied among birds, the following, though rare 62,63,68 , primary bone tumours have been described: osteoma [68][69][70] , osteosarcoma 68,71 , chondroma 68 and chondrosarcoma 64,68 . It has been reported that neoplasms are frequently seen in captive birds, yet the majority of these neoplasms were benign, and all were diagnosed as lipomas 72 .…”
Section: Differential Diagnosis Based On Phylogenetic Disease Bracketmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall avian neoplasm rate in the literature analysis was 2.3% (3298/144,277 birds; Supplementary Table S1) indicating that neoplasms are rare among birds, as also suggested by others [65][66][67] . Although neoplastic diseases are not well studied among birds, the following, though rare 62,63,68 , primary bone tumours have been described: osteoma [68][69][70] , osteosarcoma 68,71 , chondroma 68 and chondrosarcoma 64,68 . It has been reported that neoplasms are frequently seen in captive birds, yet the majority of these neoplasms were benign, and all were diagnosed as lipomas 72 .…”
Section: Differential Diagnosis Based On Phylogenetic Disease Bracketmentioning
confidence: 99%
“…However, the two pathological lesions share the majority of morphological features and their multifocal appearance makes a disseminated osseous malignancy a relevant differential diagnosis. The benign features and the extreme rarity among birds makes osteoma a rather unlikely differential diagnosis 67,69,70,73 . The lack of articular proximity and the circumferential involvement of the bone make the differential diagnosis of an osteochondroma of the left fibula also highly unlikely, whereas it remains a differential diagnosis for the pathologically altered vertebrae.…”
Section: Differential Diagnosis Based On Phylogenetic Disease Bracketmentioning
confidence: 99%
“…In birds, the body location of osteomas has been recorded with origins in the scapula, humero-radial joint [3], kidney [6], nostrils [8], sternum [11], tarsometatarsus [14], proximal radius [17], skin [21], elbow joints [22], skull [20,27], foot cushion [27], and infraorbital arch [28]. The cutaneous bilateral location of the masses in humerus radioulna junction in this report is unusual.…”
mentioning
confidence: 78%
“…Additionally, the etiology is uncertain given that historical information such as age, breed, sex, and trauma often cannot be accurately determined [8,11]. There are two proposed mechanisms for formation of lesions of osteoma cutis, a disordered embryologic process in which normal mesenchymal cells that are destined to differentiate into osteoblasts are present in the wrong location (hamartoma); and a metaplastic process, in which normal extraskeletal mesenchymal cells are stimulated to become osteoblasts by external factors [5,13,15,31].…”
mentioning
confidence: 99%
See 1 more Smart Citation